PERANCANGAN STRUKTUR BANGUNAN GEDUNG RUSUNAWA 4 LANTAI DI KOTA PONTIANAK: PERANCANGAN STRUKTUR BANGUNAN GEDUNG RUSUNAWA 4 LANTAI DI KOTA PONTIANAK - rasiwan, rasiwan; putri, riananda; Syahrani, Deny (RETENSI, 2021)
Rusunawa, which means "Simple Rental Flats", is a facility of simple residence with multi-storey buildings in order to save the increasingly narrow land use, due to community housing needs. The design of the 4-storey Rental Flats was made to reduce the problem of crowd population in the area of near the banks of the Kapuas River, Pontianak City. The 4-storey Rental Flats building was designed with a conventional reinforced concrete structure system. This structural system does not cost a lot more than precast concrete and composite steel structural systems. In addition, reinforced concrete structural systems have some advantages : durable and fire resistant, strong and sturdy, and low costs maintenance. The results of the 4-storey Rental Flats Building Structural Design include : the size of the floor slab thickness 12 cm and flat roof with 10 cm thick ; beam in dimensions of 35 cm x 70 cm, 25 cm x 50 cm, 20 cm x 40 cm, and 15.30 ; column with dimensions of 50 cm x 50 cm ; foundation with dimensions of 2 m x 4 m and 2 m x 2 meters.